Climatic and Societal Impacts of a "Forgotten" Cluster of Volcanic Eruptions in 1108-1110 CE - Ludlow, Francis (My University, 2020)
Recently revised ice core chronologies for Greenland have newly identified one of the largest sulfate deposition signals of the last millennium as occurring between 1108 and 1113 CE. Long considered the product of the 1104 CE Hekla (Iceland) eruption, this event can now be associated with substantial deposition seen in Antarctica under a similarly revised chronology. This newly recognized bipolar deposition episode has consequently been deemed to reveal a previously unknown major tropical eruption in 1108 CE. Here we show that a unique medieval observation of a “dark” total lunar eclipse attests to a dust veil over Europe in May 1110 CE, corroborating the revised ice-core chronologies. Furthermore, careful evaluation of ice core records points to the occurrence of several closely spaced volcanic eruptions between 1108 and 1110 CE. The sources of these eruptions remain unknown, but we propose that Mt. Asama, whose largest Holocene eruption occurred in August 1108 CE and is credibly documented by a contemporary Japanese observer, is a plausible contributor to the elevated sulfate in Greenland. Dendroclimatology and historical documentation both attest, moreover, to severe climatic anomalies following the proposed eruptions, likely providing the environmental preconditions for subsistence crises experienced in Western Europe between 1109 and 1111 CE.
PUBLISHED
Recently revised ice core chronologies for Greenland have newly identified one of the largest sulfate deposition signals of the last millennium as occurring between 1108 and 1113 CE. Long considered the product of the 1104 CE Hekla (Iceland) eruption, this event can now be associated with substantial deposition seen in Antarctica under a similarly revised chronology. This newly recognized bipolar deposition episode has consequently been deemed to reveal a previously unknown major tropical eruption in 1108 CE. Here we show that a unique medieval observation of a dark total lunar eclipse attests to a dust veil over Europe in May 1110 CE, corroborating the revised ice-core chronologies. Furthermore, careful evaluation of ice core records points to the occurrence of several closely spaced volcanic eruptions between 1108 and 1110 CE. The sources of these eruptions remain unknown, but we propose that Mt. Asama, whose largest Holocene eruption occurred in August 1108 CE and is credibly documented by a contemporary Japanese observer, is a plausible contributor to the elevated sulfate in Greenland. Dendroclimatology and historical documentation both attest, moreover, to severe climatic anomalies following the proposed eruptions, likely providing the environmental preconditions for subsistence crises experienced in Western Europe between 1109 and 1111 CE.
Keywords: Volcanic eruptions; Greenland; Dendrochronology; Documentary sources; Europe; Iceland; Making Ireland; Smart & Sustainable Planet; History